Animal models in tuberculosis research – where is the beef?. (August 2015) - Myllymäki, Henna; Niskanen, Mirja; Oksanen, Kaisa E; Rämet, Mika
<x xml:space="preserve">Abstract</x> Introduction: Tuberculosis (TB) is a major global health problem, and new drugs and vaccines are urgently needed. As clinical trials in humans require tremendous resources, preclinical drug and vaccine development largely relies on valid animal models that recapitulate the pathology of human disease and the immune responses of the host as closely as possible. Areas covered: This review describes the animal models used in TB research, the most widely used being mice, guinea pigs and nonhuman primates. In addition, rabbits and cattle provide models with a disease pathology resembling that of humans. Invertebrate models, including the fruit fly and the Dictyostelium amoeba, have also been used to study mycobacterial infections. Recently, the zebrafish has emerged as a promising model for studying mycobacterial infections. The zebrafish model also facilitates the large-scale screening of drug and vaccine candidates. Expert opinion: Animal models are needed for TB research and provide valuable information on the mechanisms of the disease and on ways of preventing it. However, the data obtained in animal studies need to be carefully interpreted and evaluated before making assumptions concerning humans. With an increasing understanding of disease mechanisms, animal models can be further improved to best serve research goals.